The Impact of the People's Business Credit (KUR) Programme on Entrepreneurship Development and Economic Growth in Indonesia - Syamsu Rijal; Antou, Gracela Pinkan (West Science Journal Economic and Entrepreneurship, 2024)
The People’s Business Credit (Kredit Usaha Rakyat, KUR) program has been a significant government initiative in Indonesia, aimed at promoting entrepreneurship and stimulating economic growth, particularly among micro, small, and medium enterprises (MSMEs). This study examines the impact of the KUR program on entrepreneurship development and economic growth, using a quantitative analysis based on a sample of 100 MSME entrepreneurs who have received KUR loans. Data was collected through a survey utilizing a Likert scale (1-5) and analyzed using SPSS version 25. The results show that KUR funding positively impacts business expansion, innovation, and profitability, with a significant correlation between program participation and improvements in entrepreneurship development. Furthermore, the study highlights the program’s contribution to local economic growth through job creation and increased regional economic activity. The findings indicate that the KUR program is effective in fostering entrepreneurship, particularly in rural areas, and plays a crucial role in stimulating economic growth at the local level. The study provides valuable insights for policymakers to improve the program and further support MSMEs in Indonesia.